Інноваційна культура як фактор формування інноваційно-сприятливого середовища на підприємстві - Косенко, Олександра Петрівна (НТУ "ХПІ", 2017)
Розкрита роль інноваційної культури як основи формування інноваційно сприятливого середовища інноваційного розвитку промислового підприємства. Визначено та систематизовано функції інноваційної культури, що визначають стан інноваційної культури суспільства та окремої організації. Розроблено методичні підходи до аналізу стану інноваційної культури суспільства як складової інноваційної діяльності промислового підприємства, а також до аналізу внутрішньої інноваційної культури організації як складової її потенціалу інноваційного розвитку. Результати аналізу можуть бути покладені в основу створення теоретико-методичної бази для комерціалізації інтелектуально-іноваційних технологій. В основу процесу комерціалізації запропоновано покласти теорії та практику технологічного аудиту.

The role of innovation culture as the basis for formation of innovation-friendly environment of innovative development of industrial enterprise is revealed. The functions of innovative culture that determine the state of innovation culture of a society and a separate organization are determined and systematized. The methodical approaches to the analysis of the state of the innovative culture of society as a component of the innovative activity of the industrial enterprise, as well as to the analysis of the internal innovation culture of the organization as an integral part of its potential of innovative development are developed. The results of the analysis may be the basis for the creation of a theoretical and methodological basis for the commercialization of intellectual-innovative technologies. The basis of the commercialization process is to put the theory and practice of technological audit. It is proved that with the help of technological audit, they try to put into operation the internal, hidden reserves of the enterprise to increase profits and increase profitability, to create an innovation-friendly environment.
Innovative culture as a factor in the formation of innovation-friendly environment in the enterprise
Keywords: інноваційна культура; функції впливу; інноваційна діяльність; потенціал інноваційного розвитку; технологічний аудит; комерціалізація технологій; innovative culture; functions of influence; innovative activity; potential of innovative development; technological audit; commercialization of technologies